Time interval between infective endocarditis first symptoms and diagnosis: relationship to infective endocarditis characteristics, microorganisms and prognosis. (17th February 2017) - N'Guyen, Yohan; Duval, Xavier; Revest, Matthieu; Saada, Matthieu; Erpelding, Marie-Line; Selton-Suty, Christine; Bouchiat, Coralie; Delahaye, François; Chirouze, Catherine; Alla, François; Strady, Christophe; Hoen, Bruno; et al.
Abstract: Objective: To analyze the characteristics and outcome of infective endocarditis (IE) according to the time interval between IE first symptoms and diagnosis. Methods: Among the IE cases of a French population-based epidemiological survey, patients having early-diagnosed IE (diagnosis of IE within 1 month of first symptoms) were compared with those having late-diagnosed IE (diagnosis of IE more than 1 month after first symptoms). Results: Among the 486 definite-IE, 124 (25%) had late-diagnosed IE whereas others had early-diagnosed IE. Early-diagnosed IE were independently associated with female gender (OR = 1.8; 95% CI [1.0–3.0]), prosthetic valve (OR= 2.6; 95% CI [1.4–5.0]) and staphylococci as causative pathogen (OR = 3.7; 95% CI [2.2–6.2]). Cardiac surgery theoretical indication rates were not different between early and late-diagnosed IE (56.3% vs 58.9%), whereas valve surgery performance was lower in early-diagnosed IE (41% vs 53%; p = .03). In-hospital mortality rates were higher in early-diagnosed IE than in late-diagnosed IE (25.1% vs 16.1%; p < .001). Conclusions: The time interval between IE first symptoms and diagnosis is closely related to the IE clinical presentation, patient characteristics and causative microorganism. Better prognosis reported in late-diagnosed IE may be related to a higher rate of valvular surgery. KEY MESSAGES: Infective endocarditis, which time interval between first symptoms and diagnosis was less than one month, were mainly due to Staphylococcus aureus in France. Staphylococcus aureus infective endocarditis were associated with septic shock, transient ischemic attack or stroke and higher mortality rates than infective endocarditis due to other bacteria or infective endocarditis, which time interval between first symptoms and diagnosis was more than one month. Infective endocarditis, which time interval between first symptoms and diagnosis was more than one month, were accounting for one quarter of all infective endocarditis in our study and were associated with vertebral osteomyelitis and a higher rate of cardiac surgery performed for hemodynamic indication than other infective endocarditis.